Ensino de música na educação pública: caminhos Dalcrozianos - Freitas, Crisanto Dantas Sales de (2022)
This research seeks to analyze and find answers upon the music teaching from the musical and rhythm education based on the precepts of Émile Jacques-Dalcroze (1865-1950). The plan of this research is divided into a theoretical part and a practical part: we start from readings and annotations, focusing on bibliographic research, in order to achieve a deeper theoretical interpretation. Secondly, we analyze the results to reach the main point of this study, which is the application, in a bimester, of the principles of the dalcrozian methodology in the classroom. The second stage of this research is the practical part, which is carried out in a seventh grade elementary school class at Escola Estadual João Ferreira de Souza, located in the city of Santa Cruz, RN. When appropriate, the students will experience playful activities with the experimentation of the principles of the dalcrozian methodology, with the main aim at promoting better perception and development in the teaching and learning process in the Arts/Music curricular component. During the practical interventions in the classroom, were used melodies and Afro-Amerindian rhythms of the folk group “Boi de Reis”, with the intention of bringing the educational experience closer to the community that surrounds the school. Finally, we will present the results obtained in this study in the form of a pedagogical proposal and a scientific article.